Type C Pancreaticobiliary Maljunction Is Associated With Perforated Choledochal Cyst in Children - Zhu, Linlin; Xiong, Jing; Lv, Zhibao; Liu, Jiangbin; Huang, Xiong; Xu, Weijue (Frontiers in Pediatrics, 2020)
Background Perforation of a choledochal cyst (CC) is not rare, but the pathogenesis of spontaneous perforation has not been established. Pancreaticobiliary maljunction (PBM) is commonly seen in association with choledochal cyst. To explore the relationship between PBM and perforated CC, a retrospective study was conducted. Methods We analyzed all the patients with CC who underwent surgery in our hospital from 2014.06.01 to 2018.12.31. All patients were divided into two groups: group 1 were patients with perforated CC, and group 2 were patients with non-perforated CC. We recalled all the patients records to identify types of PBM. PBM was divided into four types ((A) stenotic type, (B) non-stenotic type, (C) dilated channel type, and (D) complex type) according to the classification proposed by the Committee on Diagnostic Criteria of the Japanese Study Group on Pancreaticobiliary Maljunction (JSGPM) in 2015. Results There were 186 patients with CC in all, and 116 patients showed PBM. 20 patients in group 1 and 96 patients in group 2. There was an extremely higher percentage of type C PBM in group 1 than in group 2 (60% and 17.7%, respectively). More fusiform dilatation cases were found in group 1 (70%) than in group 2 (58.3%). Also there were more type C PBM in fusiform cases and type A PBM were frequently seen in cystic cases (P<0.01). Conclusions We found that Type C PBM and fusiform common bile duct maybe relate to the perforation of choledochal cyst. Patients with type C PBM and fusiform common bile duct should be treated more proactively, preferably before they perforate.